The impact of displacement on child health: Evidence from Colombia's DHS 2010 - Nina Wald (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper investigates the causal impact of displacement on health outcomes for Colombian children of different age cohorts. It uses the Colombian Demographic and Health Survey 2010, which provides both a number of health outcomes and information about displacement of households. Two different empirical strategies are employed to identify the impact of displacement on child health, namely a linear regression model and propensity score matching. In order to capture different dimensions of health, four health outcomes are used as dependent variables: (i) height-for-age z-scores; (ii) subjective health status; (iii) affiliation to a health insurance; and (iv) having a health problem last month. Overall, a negative relationship between displacement and child health is documented. In line with findings from African and Asian countries, displacement increases the likelihood for malnutrition for young children and primary school children. Moreover, being displaced leads to a lower subjective health status for children from all age cohorts. Yet, displaced children are not affected by health problems significantly more often than non-displaced children. Last, but not least, displaced children from all age cohorts are significantly less likely to have health insurance.
Keywords: C21; D19; I13; O54; 330; Child Health; Displacement; Armed Conflict; Colombia; Propensity Score Matching